Envisioning Accountability through a Mobile Application: a Theoretical Framework - Arafat, Md. Yeasir; Fahmida (Journal of Governance and Accountability Studies, 2025)
Purpose: The accountability of public officials is a cornerstone of democratic systems; however, citizens often struggle to oversee delegated authorities effectively because of population growth and governance complexity. This study proposes a mobile application designed to bridge this gap by enabling direct citizen engagement, real-time oversight, and transparency through an autonomous accountability committee. Methods: This theoretical study employed a qualitative, hypothesis-driven approach that integrated governance principles, technological feasibility assessments, and comparative analyses. Results: The proposed framework enables structured citizen participation in accountability processes through features such as complaint submission, voting, data audits, oversight, and investigative reporting. By aligning governance processes with democratic principles, the system fosters transparency, trust, and public administration responsibility. Conclusion: The framework for an accountability mobile application leverages technology to improve transparency, citizen engagement, and government oversight. It addresses inefficiencies in traditional systems while overcoming challenges such as data security and legal recognition. Compared with existing digital tools, this system offers stronger engagement and enforcement. Future research should focus on pilot implementations to assess their impact on governance and public trust. Limitations: As the research is entirely theoretical, practical challenges such as government adoption, cyber security risks, legal compliance, and technological scalability remain untested. The feasibility of implementation depends on institutional cooperation and regulatory adaptation. Contributions: This research advances the discourse on democratic oversight, digital accountability, and citizen empowerment in public administration. Key features include AI monitoring, blockchain security, decentralized participation, and technology-based digital mechanisms, along with existing methods to ensure an effective accountability system.